Gut Microbiome Influences the Efficacy of PD-1 Antibody Immunotherapy on MSS-Type Colorectal Cancer via Metabolic Pathway - Xu, Xinjian; Lv, Ji; Guo, Fang; Li, Jing; Jia, Yitao; Jiang, Da; Wang, Na; Zhang, Chao; Kong, Lingyu; Liu, Yabin; Zhang, Yanni; Lv, Jian; et al. (Frontiers in Microbiology, 2020)
Colorectal cancer (CRC) appears to be rather refractory to checkpoint blockers except the patient with deficient in mismatch repair (dMMR). Therefore, new advances in the treatment of most mismatch repair proficiency (pMMR) (also known as microsatellite stability, MSS) type of CRC patients are considered to be an important clinical issue associated with programmed death 1 (PD-1) inhibitors. In the present study, we evaluated the effects of gut microbiome of MSS-type CRC tumor-bearing mice treated with different antibiotics on PD-1 antibody immunotherapy response. Our results confirmed that the gut microbiome played a key role in the treatment of CT26 tumor-bearing mice with PD-1 antibody. After PD-1 antibody treatment, the injection of antibiotics counteracted the efficacy of PD-1 antibody in inhibiting tumor growth when compared with the Control group. Bacteroides_sp._CAG:927 and Bacteroidales_S24-7 were enriched in Control group. Bacteroides_sp._CAG:927, Prevotella_sp._CAG: 1031 and Bacteroides were enriched in Coli group, Prevotella_sp._CAG:485 and Akkermansia_muciniphila were enriched in Vanc group. The metabolites were enriched in the glycerophospholipid metabolic pathway consistent with the metagenomic prediction pathway in Vanc group, Prevotella_sp._CAG:485 and Akkermansia may maintain the normal efficacy of PD-1 antibody by affecting the metabolism of glycerolipid. Changes in gut microbiome leaded to changes in metabolic level, which affected the expression of immune-related cytokines IFN-γ and IL-2 in the tumor microenvironment, resulting in a different therapeutic effect of PD-1 antibody. Our findings show that changes in the gut microbiome affect the metabolic pathway, thereby regulating the therapeutic potential of of PD-1 antibody in the immunotherapy of MSS-type CRC tumor-bearing mice